Diferencialna diagnostika različnih tipov demence s pozitronsko emisijsko tomografijo (PET) - Prestreši, Leonora (Placebo, 2024)
Positron emission tomography is a non-invasive medical imaging technique that measures the three-dimensional distribution of a biologically active substance labeled with a positron emitter. It is a diagnostic technique complementary to computerized tomography and magnetic resonance imaging, as it provides the physician not only with information about the morphology of the examined tissue but also insight into its function and molecular structure. Positron emission tomography imaging plays an important role in earlier and more accurate diagnosis of different types of dementia, which is important for optimal treatment. This has become particularly important with the recent development of pathology-specific treatments for Alzheimer's disease, and as these continue to evolve, there will be an increased need to introduce methods to include the most suitable candidates in new treatments.
Keywords: 18F-FDG PET možganov; amiloidni PET možganov; Demenca; PET; tau PET